LEVERAGING DEEP LEARNING APPROACH FOR ACCURATE ALPHABET RECOGNITION THROUGH HAND GESTURES IN SIGN LANGUAGE - Nugroho, Nadiyan Syah Wahyu; Putra, Muhammad Pajar Kharisma (Informatika, Universitas Jenderal Soedirman, 2025)
Sign language is one way of communication used by people who cannot speak or hear (deaf and speech impaired), so not everyone can understand sign language. Therefore, to facilitate communication between normal people and deaf and speech-impaired people, many systems have been created to translate gestures and signs in sign language into understandable words. Artificial intelligence and computer vision-based technologies, such as YOLOv9 offer solutions to recognize hand gestures more quickly, accurately, and efficiently. This research aims to develop a hand gesture detection system for alphabetic sign language using YOLOv9 architecture, with the aim of improving the accuracy and speed of hand gesture detection. The data used consists of 6500 sign language alphabet hand gesture images that have been labeled with bounding boxes and processed using image augmentation techniques. The model was trained on the Kaggle platform and evaluated using performance metrics such as Accuracy, Precision, Recall, F1-Score, and Intersection over Union (IoU). The results show that the YOLOv9 model achieves an average detection accuracy of 97%, with precision and recall above 90% for most classes. In addition, YOLOv9 shows advantages over other algorithms such as SSD MobileNet v2 and Faster RCNN, both in terms of speed and accuracy. In conclusion, YOLOv9 proved to be very effective in detecting sign language hand gestures, thereby speeding up and facilitating communication. This research is expected to contribute to the development of more inclusive technologies in various fields, such as education, public services, and employment opportunities, which support better communication between sign language users and the general public.